2020
DOI: 10.47405/mjssh.v5i5.402
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction and Commuter Service: An Evaluation of Intercity Keretapi Tanah Melayu Berhad (KTMB) Performance Delivery

Abstract: The present study focuses on an evaluation of intercity Keretapi Tanah Melayu Berhad (KTMB) performance delivery on customer satisfaction and commuter services. Its objective is to evaluate the customers’ satisfaction of KTMB intercity towards the performance delivery of various services. As such, a framework was proposed for major dimensions which have an impact on the level of services satisfaction provided by my KTM commuter. Furthermore, the study employed qualitative and quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Inefficiency of employees, lack of management commitment, train timeliness and bad service at ticketing counters are among the problems cited. In addition, employees should be more empathic, courteous, and professional in their work (Bambale et al, 2020;Ibrahim et al, 2019Ibrahim et al, , 2021Isai et al, 2020). These studies demonstrated the importance of rail employees performing their duties diligently and consistently.…”
Section: Introductionmentioning
confidence: 83%
“…Inefficiency of employees, lack of management commitment, train timeliness and bad service at ticketing counters are among the problems cited. In addition, employees should be more empathic, courteous, and professional in their work (Bambale et al, 2020;Ibrahim et al, 2019Ibrahim et al, , 2021Isai et al, 2020). These studies demonstrated the importance of rail employees performing their duties diligently and consistently.…”
Section: Introductionmentioning
confidence: 83%
“…In this study, customer satisfaction is the main dependent variable to be tested. Customer satisfaction, as explored by Choy & Salleh (2022) and Isai et al (2020), is the positive response customers experience after consuming goods or services that meet their requirements and needs. This satisfaction is integral to an operational overall success, directly influencing its sustainability due to repeated action.…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…Nor and Rahim's (2021) study in Penang further underscores the critical role of reliability, tangible, and responsiveness in satisfying rail transport passengers. The importance of avoiding poor services is emphasized, as it can lead to customer complaints and tarnish a company's corporate image thus affecting the shift (Isai et al, 2020).…”
Section: Customer Satisfactionmentioning
confidence: 99%
“…On the other hand, side running indicates trains powered by a third rail system. While not classified as high-speed railways, these systems do significantly contribute to facilitate intracity and intercity transportation within Malaysia [4]. The pantograph-catenary system is illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%